Long‐term follow‐up of endoscopic therapy for stenosis of the biliobiliary anastomosis associated with orthotopic liver transplantation. Issue 6 (28th May 2013) - Albert, Jörg G.; Filmann, Natalie; Elsner, Julia; Moench, Christian; Trojan, Jörg; Bojunga, Jörg; Sarrazin, Christoph; Friedrich‐Rust, Mireen; Herrmann, Eva; Bechstein, Wolf Otto; Zeuzem, Stefan; Hofmann, Wolf Peter
<x xml:space="preserve">Abstract</x> Endoscopic treatment for stenosis of an anastomotic biliary stricture (ABS) after orthotopic liver transplantation (OLT) has been proven to be effective and safe, but the long‐term outcomes and the risk factors for recurrence are unknown. All 374 patients who underwent OLT at Frankfurt University Hospital were screened for the occurrence of ABSs. ABSs were treated via the endoscopic insertion of a plastic endoprosthesis (29.8%), balloon dilation (12.8%), or a combination of the two (57.4%). The mean follow‐up time was 151 weeks, and the mean survival time was 3.4 years. ABSs were observed in 47 patients (12.6%). The mean time from OLT to an ABS was 16.25 months (median = 3.25 months). The cumulative incidence rates for ABSs were 0.09 after 12 months, 0.10/24 m. and 0.11/36 m. In 12 cases (25.5%), ABSs were observed more than 12 months after OLT. ABSs recurred in 16 of the 47 patients (34%). The occurrence of an ABS 6 weeks or more after OLT was a significant predictor of ABS recurrence [P = 0.04, hazard ratio (HR) = 0.235]. There was a trend of hepatitis C virus (HCV) infections being predominant in patients experiencing ABS recurrence (30% for HCV etiology versus 4% for non‐HCV etiology) in comparison with patients not experiencing recurrence (36% for HCV etiology versus 30% for non‐HCV etiology, P > 0.05). The severity of the initial stricture predicted ABS recurrence (P = 0.046, HR = 2.78), but it did not influence overall survival. The long‐term resolution of ABSs was observed in 45 of the 47 patients (95.7%), and ABS recurrence was treated with another attempt (n = 16 or 34%) or 2 more attempts (n = 1) at endoscopic treatment. In conclusion, the long‐term success of the endoscopic treatment of ABSs is highly probable if recurrent strictures are again treated endoscopically. ABSs might occur late (>36 months) after OLT, and lifelong follow‐up is essential for identifying OLT patients with ABSs. Liver Transpl 19:586–593, 2013. © 2013 AASLD.